PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR - Isna Alifia Aghniyah; Fitri Nuraeni; Nadia Tiara Antik Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Speaking skills are one of the essential aspects in Indonesian language learning at the elementary school level, yet students’ speaking abilities remain relatively low. This study aims to analyze the influence of the Snowball Throwing and Talking Stick models on the speaking skills of fifth-grade elementary students, as well as to compare the improvement in speaking skills between these two models. The research method employed is a Quasi Experimental Design in the form of a Nonequivalent Control Group Design. The research sample consists of two classes: the experimental class applying the Snowball Throwing model and the control class applying the Talking Stick model, each with 29 students. Instruments used include pre-test and post-test assessments and observation sheets for teacher and student activities. Data analysis was conducted using descriptive and inferential statistics with IBM SPSS version 30.0. The results show that 1) The cooperative learning model Snowball Throwing has an effect of 57.4% on improving students’ speaking skills, 2) The cooperative learning model Talking Stick has an effect of 55.6%, 3) The average N-Gain value for speaking skills in the experimental class is 0.4786 (moderate category), while in the control class it is 0.3775 (low category). Based on the t-test, there is a significant difference in the improvement of speaking skills between the two classes, with the Snowball Throwing model being more effective than the Talking Stick model. This research recommends the use of the cooperative learning model Snowball Throwing as an alternative to enhance elementary students’ speaking skills.